2018
DOI: 10.1093/gbe/evy152
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Genomic Diversity in a Neisseria meningitidis Clone Through a Colonization Bottleneck

Abstract: Neisseria meningitidis is the leading cause of epidemic meningitis in the “meningitis belt” of Africa, where clonal waves of colonization and disease are observed. Point mutations and horizontal gene exchange lead to constant diversification of meningococcal populations during clonal spread. Maintaining a high genomic diversity may be an evolutionary strategy of meningococci that increases chances of fixing occasionally new highly successful “fit genotypes”. We have performed a longitudinal study of meningococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…As in earlier studies, population bottlenecks and strong geographical signals are commonly observed. In one study, endemic MenA ST-2859 isolates (a member of cc5) were completely replaced by MenW ST-2881 isolates before reemerging as a highly clonal outbreak [161]. The authors suggest that competition with introduced MenW isolates caused a genetic bottleneck and that the reemerged ST-2859 clone may represent selection for a high-fitness variant of this lineage.…”
Section: Microevolution During Epidemics and Outbreaksmentioning
confidence: 99%
“…As in earlier studies, population bottlenecks and strong geographical signals are commonly observed. In one study, endemic MenA ST-2859 isolates (a member of cc5) were completely replaced by MenW ST-2881 isolates before reemerging as a highly clonal outbreak [161]. The authors suggest that competition with introduced MenW isolates caused a genetic bottleneck and that the reemerged ST-2859 clone may represent selection for a high-fitness variant of this lineage.…”
Section: Microevolution During Epidemics and Outbreaksmentioning
confidence: 99%